2022
DOI: 10.1186/s12870-022-03865-6
|View full text |Cite
|
Sign up to set email alerts
|

Cellular messengers involved in the inhibition of the Arabidopsis primary root growth by bacterial quorum-sensing signal N-decanoyl-L-homoserine lactone

Abstract: Background N-acyl-homoserine lactones (AHLs) are used as quorum-sensing signals by Gram-negative bacteria, but they can also affect plant growth and disease resistance. N-decanoyl-L-homoserine lactone (C10-HSL) is an AHL that has been shown to inhibit primary root growth in Arabidopsis, but the mechanisms underlying its effects on root architecture are unclear. Here, we investigated the signaling components involved in C10-HSL-mediated inhibition of primary root growth in Arabidopsis, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…In addition, the activation of plasma membrane Ca 2+ channels might be involved in AHL priming. 23 , 24 Furthermore, the effects of C10-HSL on increased reactive oxygen species (ROS) and nitric oxide (NO) production could be significantly alleviated by inhibiting the activity of Ca 2+ channels. 23 Overall, these studies indicated that the initial response to AHL partially depends on the regulation of Ca 2+ -signaling.…”
Section: Other Potential Signals Involved In Ahl Primingmentioning
confidence: 99%
“…In addition, the activation of plasma membrane Ca 2+ channels might be involved in AHL priming. 23 , 24 Furthermore, the effects of C10-HSL on increased reactive oxygen species (ROS) and nitric oxide (NO) production could be significantly alleviated by inhibiting the activity of Ca 2+ channels. 23 Overall, these studies indicated that the initial response to AHL partially depends on the regulation of Ca 2+ -signaling.…”
Section: Other Potential Signals Involved In Ahl Primingmentioning
confidence: 99%